Synthesis, characterization and photo catalytic degradation of aqueous eosin over Cr containing Ti/MCM-41 and SiO2-TiO2 catalysts using visible light - Awate, S. V.; Jacob, Nalini E.; Deshpande, Suvarna S.; Gaydhankar, T. R.; Belhekar, Anagha A. (Journal of Molecular Catalysis A - Chemical, 2005)
Two series of samples were prepared namely Cr-Ti/MCM-41 and Cr/SiO2-TiO2 keeping Si/Ti mole ratio same, with different Cr loading. The physico-chemical properties of the samples were characterized by different analytical techniques such as XRD, FTIR, TEM, low temperature N-2 sorption, and UV-vis diffused reflectance spectroscopy. The impregnated TiO2 was in anatase form. The crystallite size was determined from Scherrer equation as well as by TEM. There is a difference between the shapes of nitrogen adsorption isotherms with and without Cr-loaded Ti/MCM-41 samples. The rate of nitrogen adsorption was found to increase with decrease in Cr content at lower P/P-0 for Cr-Ti/MCM-41 samples due to the blocking of the pores with Cr. All MCM-41 samples exhibited pore sizes from 24 nm to 32 nm. UV-vis diffused reflectance spectra of all Cr-loaded samples showed red shift of their absorption edges. Photo degradation of eosin dye was studied using visible light. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Cr-Ti/MCM-41; Cr/SiO2-TiO2; eosin; photo degradation; visible light